Sistem Pembayaran Otomatis Berbasis Contactless Smartcard Dengan Teknologi RFID di Kantin SMK Taman Harapan Bekasi - Kristanti, Ayu Dian; Setyadi, Didik (Program Studi Informatika Fakultas Ilmu Komputer Universitas Bhayangkara Jakarta Raya, 2021)
During a pandemic, we must reduce physical contact both with other people and with objects around us. With automatic payments using RFID technology based on the Internet of Things and websites to minimize physical contact (contactless smartcards) and minimize fraud in transactions. The system uses RFID sensors, Nodemcu esp8266, Jumper cables, I2c LCDs, and databases. Using the Prototype method that works continuously through collaboration between users and analysts. The contactless smartcard system at the SMK Taman Harapan Bekasi canteen can make transactions easier in the canteen. The contactless smartcard was created using the NodeMCU Esp8266 by utilizing the rfid mifare522 sensor as a tag detector so that it can facilitate the buying and selling process, for monitoring it has used a website with data that has been automatically stored in the database to find out canteen and admin user information and transaction history is saved to the database in real time.